Effect of Pursed-Lips Breathing on Quality-of-Life Chronic Obstructive Pulmonary Disease Patients with The Short Form-36 (SF-36) - Widiatmoko, Widiatmoko; Riyanto, Bambang Sigit; Retnowulan, Heni (Acta Interna The Journal of Internal Medicine, 2023)
Background. Chronic obstructive pulmonary disease (COPD) is a disease of high prevalence that is characterized by irreversible airway obstruction. The most frequent symptoms such as tightness during activity and fatigue have a negative impact on the quality of life of patients and limit physical activity in everyday life. One of the goals of COPD therapy is to improve the quality of life of patients. Pursed-Lips Breathing (PLB) as one of the pulmonary rehabilitation options is known to improve breathing patterns, increase tidal volume, and reduce shortness of breath.Objective. To demonstrate the influence of PLB on the quality of life of COPD patients as measured by The Short-Form 36 questionnaire.Methods. A prospective, single-blind, randomized controlled trial study was conducted at RSKP Paru Respira, Bantul, Yogyakarta. The subjects of the study were stable COPD patients who met the inclusion and exclusion criteria. The SF-36 score was assessed in both groups before and after 28 days (4 weeks). The independent variable PLB treatment and the dependent variable SF-36 score were measured before and after treatment. Statistical analysis was carried out by a mean difference test between the treatment group and the control group.Results. Seventy-eight patients (mean age, 63 years) were randomized into the treatment group (n=41 patients) continuing standard therapy and doing 8-minute PLB for 28 days and the control group (n=37 patients) only continuing the previous standard therapy. The PLB treatment group showed an increase in the mean delta of the SF-36 score which was especially significant in aspects of physical function, physical role, and social function. There was a significant difference in the increase of average total SF-36 score in the PLB treatment (8.93 ± 15.85) compared to the control group (2.09 ± 8.15) of the 100 points total score (p=0.033).Conclusion. There was an improvement in the SF-36 score in COPD patients who received standard therapy and pulmonary rehabilitation with a PLB technique for four weeks.